(untitled) (Clinics, 2021)
OBJECTIVES: To evaluate the mean concentration of 25-hydroxivitamin D [25(OH) D] and prevalence of hypovitaminosis D in individuals residing in Rio de Janeiro, Brazil. METHODS: The data of 80,000 consecutive individuals who had 25(OH) D measurements performed by electrochemiluminescence between 1/2/2018 and 2/5/2018 were selected. Patients who reported the use of therapies/ supplements were excluded. Levels of 25(OH) D X20 ng/mL (ages o60 years) and X30 ng/mL (ages X60 years) were considered adequate. RESULTS: We analyzed the data of 24,074 individuals (1–95 years old, 64.7% female). Descriptive curves showed that, in both sexes, the mean values of 25(OH) D decreased from the first years of life until adolescence, then slightly increased, and then tended to stabilize during adulthood. Levels of 25(OH) D o20 ng/mL were observed in 6% of girls versus 3.6% of boys and in 13.6% of adolescent girls versus 12.6% of adolescent boys and 11% of adults. The percentage of seniors with serum levels of 25(OH) D o20 ng/mL was 13.6% in women and 12.7% in men; 53.2% of women and 50.6% of men had levels o30 ng/mL. CONCLUSIONS: Mean 25(OH) D values were higher in children and lower in adolescents and women. Approximately 90% of non-seniors and presumably healthy residents of the urban metropolitan region of Rio de Janeiro presented satisfactory levels of 25(OH) D during the summer months; however, in over half of the elderly, the serum concentrations of 25(OH) D were inadequate. Therefore, strategies for the prevention of hypovitaminosis D should be considered in the senior population.